Propriedades físico-hídrico-mecânicas e modelos de capacidade de suporte de carga do solo submetido a diferentes sistemas de manejos - Andrade, Maria Luiza de Carvalho (2018)
The objective of this work was to evaluate the physical-hydrological and physical-mechanical properties and a typical dystrophic latosol under a croplivestock-forest integration system (CLFI) with one (CLFI 1 year) and six (CLFI 6 years) years of implantation, pasture, and native cerrado (NC) on soil horizons A, AB, BA top, BA base, and Bw. Another objective was to propose loadbearing capacity models (LBCM) for horizons A, AB, BA top, and BA base, and identify which management most affects soil compaction. Sixty undisturbed samples were collected to determine the curves of water-retention in the soil, total porosity, microporosity, macroporosity, and bulkdensity. The field capacity, permanent wilting point, and available water capacity were also determined. Thirty-six undisturbed samples were collected from horizon A to establish the saturated soil water conductivity (Ks), which was obtained trough assays conducted with constant load permeameter. One hundred and twenty undisturbed samples were collected to determine the soil resistance to penetration (RP) and preconsolidation pressure (p), and, 240 undistuberd samples were used for the LBCM. Regarding the physical-hydrological properties, the management in the pasture area degraded the soil structure in horizons A and AB. The horizons A and BA top showed the degradation of the soil structure in the distinct treatments in the following order: NC < CLFI 1 year, CLFI 6 years < pasture. The integrated systems exerted less impact on the soil structure and presented soil physical and hydrological properties similar to the NC in the horizon AB. All the types of management reduced the Ks in horizon A. For the physical-mechanical attributes, the soil moisture influenced the RP and p. The p was influenced in all types of management and horizons evaluated. The structures of horizons A and AB of the pasture were the most degraded. The LBCM showed that the soil compaction caused by pasture and 1-year CLFI was higher in horizons A and AB. The NC presented a lower loadbearing capacity in horizons A and B. There was no significant difference between the LBCM of the pasture, CLFI 1 year, and CLFI 6 years in the superficial and subsurface horizons.